Proposta de planejamento estratégico para uma empresa júnior de engenharia industrial - LOUSADA, Ana Caroline Louzada e (2019)
This work has as objective to develop a proposal of strategic planning for a junior industrial engineering company as a way to add to its development and strategic position in the market in which it operates. For this purpose, a research was conducted described as qualitative to analyze which positive and negative factors that influence such development and this way, it was determined which measures would be taken to the development if a strategic planning for the company studied, amongst them, the ones that stand out the most are: environmental analysis, development of SWOT matrix, establishment of organizational guidelines and creation of action plans that have strategies and indicators to support the achievement of the strategic objectives outlined.